ANALISIS HUBUNGAN COST EFECTIVENESS MAHASISWA PENGHUNI ASRAMA DENGAN PRESTASI BELAJAR - Vira Maratus Sholihah; Mukhamad Zulfikar Lutfi; Asep Sunandar; Maulana Amirul Adha (re-JIEM (Research Journal of Islamic Education Management), 2020)
This study aims to, (1) determine the cost effectiveness analysis of UM dormitory students, who are in the faculties of the State University of Malang (UM); (2) knowing student achievement in UM environment faculties; and (3) knowing the relationship between cost effectiveness analysis of UM dormitory students to study achievement in UM faculties. This research uses a quantitative approach with a descriptive correlational research design. The instrument of this study was to use the Google form survey assistance with respondent are students of UM dormitory in UM environmental faculties. The analysis technique used in this research is descriptive analysis and correlation. The results of this study indicate: (1) the level of cost effectiveness analysis of the occupants of UM student dormitory residing in the faculties of the State University of Malang is classified as a rarity that uses cost effectiveness analysis in managing finances for dormitory and educational needs; (2) the level of learning achievement that is spread in all faculties at the State University of Malang tends to be poor; and (3) the results of the study show that there is a relationship between cost effectiveness analysis of UM student dormitory students on learning achievement.